Corpos se (mo)vendo com imagens e afetos: dança e pedagogias culturais - Odailso, Sinvaldo Berté (2014)
Anchored in a qualitative perspective, particularly in the bricolage approach, this research is articulated through a creative-pedagogical process in dance developed with a focal group that worked relationships between body and image and allowed reflections on pop culture, performativity and cultural pedagogies. The focus of the investigation is on manifestations of affects drowned from experiences with bodies and images in contexts of cultural pedagogies and in accordance with the principles of visual culture education and dance. Aspects of my own trajectory, especially affective investments directed to the pop singer Madonna, to the choreographer Pina Bausch and to the painter Frida Kahlo, motivate autobiographical narratives, methodological orientation and ways of discussing image as an artifact, an idea and an action of the body. Productions of the three arti sts build the theoretical basis to discuss affect, body and images as links between the experiences/narratives of the collaborators, fragments of my trajectory, and learning arising from the creative-pedagogical process. Images, performances and cultural a rtifacts both mine and of the collaborators, intertwine installing poignant questions about how affects can impact and change our motivations, choices and actions. The thesis faces problems over how cultural pedagogies can educate the body constituting challenges to art teaching and particularly for teaching dance. It also examines how institutionalized spaces may consider and value affects, experiences and learning that bodies bring and set in motion at school and university. From the perspective of visual culture education, I observe, describe, and analyze propositions of teaching and creation in which affective and every day life movements become allies in dance allowing insights, reflections, learning, and performative positions with which bodies can move and see. .